Chinese officers in Cirebon - Haryono, Steve (UI Scholars Hub, 2017)
The city of Cirebon was not as large as Batavia (Jakarta) or Semarang, but its location on the northern shore of Java made it an important harbour city from which the inland regions of the southern part of West Java could be serviced. As a harbour town, Cirebon became the regional centre of trade and commerce, and many Chinese immigrants settled there. As were other cities, Cirebon fell under the governance of the VOC and later of the Netherlands Indies administration A Chinese officer was appointed to deal with Chinese community issues in the region. With the exception of the well-known Major (Majoor der Chinezen) Tan Tjin Kie, whose funeral is described in his son's book, little is known about the other Chinese officers in Cirebon. Most publications concentrate on the Chinese officers in Batavia or Semarang or in other large cities. Numerous Chinese officers were appointed in Cirebon and in the surrounding regions. Many of them were members of four or five big families. This article describes their lives, families, and descendants, their businesses, and their whereabouts.